PERAN PSIKOLOGI DALAM PROSES DAKWAH - Sitti Rahmatiah (Al-Irsyad Al-Nafs : Jurnal Bimbingan dan Penyuluhan Islam)
Da'wah is an attempt to influence others to act and behaves like what is desired by Dai. As psychological beings, humans are creatures of thought and wills and human beings have a different way of thinking and feeling with each other. Therefore, it is necessary to understand how Mad'u that what is delivered by dai easily been well received. Preaching with the psychological approach (persuasive) allows people to following the will of the Mad'u, but they felt was following the will of itself.